Antenatal care services in rural Uganda: missed opportunities for good-quality care - Conrad, Paul; De Allegri, Manuela; Neuhann, Florian; Müller, Olaf; Sarker, Malabika (Qualitative health research, 2012)
Experience from countries that have achieved low maternal mortality suggests that access to good-quality maternity services is critical to improve maternal health. In this article we appraise the quality of antenatal care (ANC) services in a rural district of Uganda. We used a mixed methods approach, relying on a combination of semistructured interviews with both clients and providers, structured observations of provider-patient interactions, and infrastructure assessment of selected health facilities. We found several bottlenecks in health service delivery, including ineffective organization of educational sessions; selective omission of certain services; lack of explanation of important clinical and laboratory procedures; failure to link the performed procedures with preventive information; and occasional lack of respect for clients. The policy implications of these findings are discussed in relation to the need to (a) ensure an adequate supply of medical equipment and drugs, (b) enhance health workers’ compliance with ANC guidelines, and (c) combine medical procedures with educational messages.